Four Important Characteristics of Women in Confucianism and Its Contribution to the Implementation of Gender Equality in Vietnam - Vo, Dung Van (Conatus - Journal of Philosophy, 2024)
Four important virtues of a woman in the Confucian perspective include Works (being chaste, monogamous, and a virgin when married), Comportment (beauty), Speech, and Conduct (morality, Ethics). These virtues have profoundly influenced the conception of the role of women in traditional Vietnamese culture. Excessive focus on family roles and traditional values limits women's opportunities and rights in the public, political and economic spheres. However, in recent years, Vietnam has made significant progress in realizing gender equality. Investments in education, legal rights, and economic and social development have opened up many opportunities for women to participate in the public sector and contribute to the country's development. In this article, we will focus on clarifying issues such as: Presenting and analyzing four important women's virtues from the point of view of Confucianism in the Pre-Qin period; Finding answers to the questions raised and pointing out the contribution of four important women's virtues from a Confucian point of view in realizing gender equality in Vietnam.